THE DIFFERENCE OF SATISFACTION LEVEL IN JAMINAN KESEHATAN NASIONAL (JKN) AND GENERAL PATIENTS TOWARDS QUALITY OF DENTAL HEALTH SERVICES AT DENTAL CLINIC IN WEST KALIMANTAN (Research report) - Erdianto Setya Wardhana; Sandy Christiono (FKG Unlam, 2019)
Background: Patient perception is reckoned as one of main indicators in health service standards. Several studies have revealed that health services in hospital are perceived to be different between general patients and JKN participants, where general patients get better health services than JKN participants. Purpose : The purpose of this research is to determine the differences in the level of satisfaction between JKN patient and general patients on the quality of dental health services at dental clinic of Dr. Rubini Hospital, Mempawah - West Kalimantan. Method: This descriptive analytic study was conducted at outpatient care service, dental clinic of Dr. Rubini General Hospital, Mempawah - West Kalimantan. The research involved 80 patients, consisting of 40 JKN participants and 40 general patients aged >15 years without syndrome complications and non-complicated dental extraction patients. Patient satisfaction was measured by the SERVQUAL method which disclosed the difference in perception scores towards the expectation score on quality of service. The quality of service consists of several dimensions including reliability, responsiveness, assurance, tangible evidence, and empathy. Differences in satisfaction level of JKN participants and general patients were then analyzed by Mann-Whitney test. Results: The results showed that there were differences in SERVQUAL scores of overall quality of service between general patients and significant JKN participants (p <0.05). Conclusion: General patients have higher level of satisfaction than patient of JKN participants.